PENGARUH PEMBELAJARAN NUMERASI TERHADAP KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA DI KELAS V SDN 1 PALU - Yudani, Ni Kadek; Kertayasa, I Ketut; Sudarsana, Wayan (STAH Dharma Sentana Sulawesi Tengah, 2025)
Reinforcement related to numeracy is currently very much needed by Indonesian students. This study aims to determine the effect of numeracy learning on students' ability to solve mathematical story problems in class V SDN 1 Palu. Using a quantitative pre-experimental method of one group pretest-posttest design. Determination of the sample using a non-probability sampling technique with a saturated sampling type. The sample used in data processing was 26 students from a total initial sample of 33 students. The research instruments included teaching modules, test questions, validation sheets, interview guidelines, and documentation. Data analysis used prerequisite tests and hypothesis tests. The test results using the paired sample T-Test showed a significance value of 0.000 (sig. 2 tailed < 0.05) meaning that was accepted and was rejected. This proves that there is a significant effect of numeracy learning on students' ability to solve mathematical story problems in class V SDN 1 Palu. The obstacles for students in solving mathematical story problems lie in the difficulty of understanding concepts, calculation accuracy, and process skills. However, students' responses to numeracy learning were very positive. Students expressed their enjoyment of the applied numeracy learning and the increase in abilities they felt.